Erratum to: Intraoperative transösophageale Echokardiographie in der Herzchirurgie mit Fokus auf die Mitralklappenrekonstruktion (Zeitschrift für Herz-,Thorax- und Gefäßchirurgie, (2024), 38, 1, (37-51), 10.1007/s00398-023-00631-0) - Krajinovic, Ljubica; Fechner, Jörg; Einhaus, Friedrich; Francis, Roland; Nooh, Ehab; Czesla, M.; Dewald, Oliver; Heim, Christian (Zeitschrift für Herz-, Thorax- und Gefäßchirurgie, 2024)
CRIS-Team Scopus Importer:2024-03-29

Intraoperative transösophageale Echokardiographie in der Herzchirurgie mit Fokus auf die Mitralklappenrekonstruktion - Krajinovic, Ljubica; Fechner, Jörg; Einhaus, Friedrich; Francis, Roland; Nooh, Ehab; Czesla, M.; Dewald, Oliver; Heim, Christian (Zeitschrift für Herz-, Thorax- und Gefäßchirurgie, 2024)
Transesophageal echocardiography (TEE) is important for rapid assessment of biventricular function, regional contractility disorders and the integrity of heart valve anatomy and function. Mitral valve regurgitation (MVR) is the second most common valvular heart disease in Europe after aortic valve stenosis. Qualified TEE is indispensable for the success of minimally invasive repair of severe MVR (MIR-MVR). For quantification of MVR the vena contracta area, effective regurgitant orifice area (EROA) determined using the proximal isovelocity surface area (PISA), regurgitant volume and left ventricular endsystolic diameter are utilized for quantification of MVR. Grading of the MVR, the final assessment of the operation results and echocardiographic guidance during critical surgical steps of MIR-MVR are essential. The MIR-MVR is complex and requires an optimal interdisciplinary cooperation.
CRIS-Team Scopus Importer:2024-02-02
Keywords: Diagnostic imaging; Endoaortic occlusion; Heart-lung machine; Minimally invasive surgical procedures; Mitral valve regurgitation

Quantification of Remimazolam Besylate (CNS7056B) and Its Metabolite (CNS7054X) by LC-MS/MS in Human Plasma Using Midazolam-d4 Maleate as Internal Standard - Schmidt, Stefanie; Krajinovic, Ljubica; Mertens, Christian; Schramm, Lisa; Schüttler, Jürgen; Fechner, Jörg (Journal of Chromatographic Science, 2022)
A new assay was developed to measure the concentration of remimazolam besylate (CNS7056B) and its major carboxylic acid metabolite (CNS7054X) in human plasma. For this new assay method, midazolam-d4 maleate was used as an internal standard. After setting up a previously described assay method, using CNS7056-d4 and CNS7054-d4 as internal standards, analytical results of both methods were compared. For the new analytical method, ultra-high-performance liquid chromatography (UHPLC) with tandem mass spectrometry was applied. A purification method, using solid phase extraction, was developed and validated. The chromatographic separation of the analytes was achieved with a mobile phase gradient using a Water Acquity (TM) UHPLC-System. The Kinetex (TM) biphenyl 50 x 2.1 mm UHPLC column was used with a particle diameter of 1.7 mu m (Phenomenex, Germany). A measuring range of 0.6-2,000 ng/mL for CNS7056B and of 6-20,000 ng/mL for CNS7054X could be achieved with this new assay. The lower limit of quantification was 0.6 ng/mL for CNS7056B and 6 ng/mL for CNS7054X. The assay was validated according to US Food and Drug Administration guidelines. The new method showed an accuracy of 96.9-110.4% and a precision of 2.1-6.7% for both analytes.
CRIS-Team WoS Importer:2022-12-23